Demography, financial openness, national savings and external balance - Michael Graff; Kam Ki Tang; Jie Zhang (ETH Zurich, KOF Swiss Economic Institute, 2008)
This paper examines the impact of demographic factors on saving, investment, and external balances. We derive a number of semi-structural equations from national accounting principle and the principle that external balances for the world as a whole must sum to zero. The resulting equations embody both closed, partially open and completely open economies as special cases, and are arguably more properly specified than those previously used in the literature. We apply these semi-structural equations to a large panel data set. While our findings by and large are in agreement with most previous studies, our semi-structural equations give much more plausible estimation results for saving and investment than conventional specification.
Keywords: E21; F32; J10; 330; Demography; openness; saving; investment; current account; panel data; Bevölkerungsentwicklung; Außenhandelsliberalisierung; Sparen; Privater Haushalt; Leistungsbilanz; Panel; Schätzung; Australien